EFEKTIVITAS PENGELOLAAN SAMPAH DALAM MEWUJUDKAN KOTA SEMARANG BERSIH (Studi Kasus : Pengelolaan Sampah di TPA Jatibarang) - Tia Arfani S.R; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
Semarang City is a densely populated city with a fairly high mobility. The large number of residents, both natives and immigrants, causes many changes, one of which is the production of waste. Effective waste management is absolutely necessary so that the waste produced can be managed properly. With effective management, it is hoped that Semarang will become a clean city. This problem received a response from the government through the Environmental Service so that it was followed up. One of them is waste management at the Jatibarang TPA. This study uses the theory of effectiveness from several experts and uses the reference to the effectiveness criteria proposed by Gibson. This study uses a qualitative descriptive method conducted through interviews and also documentation. The results of the study indicate that the waste processing at the Jatibarang TPA is quite effective. Adjustment of needs with waste management innovations that are continuously improved so that problems can be resolved. The main obstacle felt was regarding funding for several facilities and infrastructure, the overwhelming need with the funds provided was felt to have not been fulfilled. The advice given is to increase public awareness to reduce waste generation so that waste can be controlled and the burden of the landfill will be reduced.